Comparative interpretation of literary irony in the works of Shakespeare and Uygun and its reflection in translation - AbduqodirovaMadinaAbduqayumqizi (Academia One, 2025)
This study examines how irony is used in the works of Shakespeare and the Uzbek writer Uygun, comparing their styles and approaches. It looks at how irony works in different cultures and how it changes when translated from English to Uzbek. The research also discusses the translator’s role in keeping the original meaning and feeling of irony, offering ideas for better translation methods. The work adds value to studies in literature and translation by showing how cultural differences affect the understanding of irony
Keywords: Irony; Shakespeare; Uygun; literary translation